Decreased hepcidin levels are associated with low steady-state hemoglobin in children with sickle cell disease in Tanzania - Lee, N; Makani, J; Tluway, F; Makubi, A; Armitage, AE; Pasricha, S-R; Drakesmith, H; Prentice, AM; Cox, SE (Elsevier, 2018)
Background The contribution of hepcidin as a regulator of iron metabolism & erythropoiesis on the severity of anemia in sickle cell disease (SCD) remains poorly characterized, especially in Sub-Saharan African populations. The aims of the study were to determine if hepcidin is associated with severity of steady-state anemia in SCD and to investigate factors associated with hepcidin and anemia in SCD. Methods Archived samples from 199 Tanzanian children, 56% boys aged 3–18 with laboratory-confirmed SCD were analysed based on recorded averaged steady-state hemoglobin (ASSH) quartiles (lowest vs. highest). Univariable and multivariable logistic regression was used to assess associations with ASSH quartiles. Findings In univariable analysis, hepcidin <5·5 ng/mL was associated with increased odds of being in the lowest ASSH quartile (OR 2·20; 95%CI 1·2–3·93) but which was limited to girls (OR 4·85, 95%CI 1·79–13·09, p = .046 for interaction). In multivariable analyses including either reticulocyte percentage or erythropoietin, lower hepcidin remained significantly associated with lowest ASSH quartile, although the hepcidin-sex interaction no longer reached statistical significance. No associations with ASSH quartile were observed for markers of inflammation, hemolysis or potential iron markers except for microcytosis, associated with higher ASSH, but which was confounded by reticulocyte percentage and alpha-thalassaemia status. Interpretation Hepcidin is lower in more severely anaemic children with SCD independent of inflammation or markers of erythropoiesis.